Des franges du projet urbain au projet de frange urbaine - Sophie Bonin; Monique Toublanc; Pierre Dérioz; Philippe Béringuier (Projets de Paysage)
Based on a cross-analysis of the body of different urban planning documents, the discourses of urban and landscape designers developing the notion of the urban fringe, and field studies in three French regions, this article explores the different meanings associated with the contact area between the built up urban space and the natural and agricultural spaces surrounding it. The perspective is historical, namely in the case of the Paris region, and geographic in the cases of sites in the Ile-de-France region, overseas (East coast of Reunion island) and in the region of Languedoc (Narbonne). How does the notion of the urban fringe conceived by urban and landscape designers, which has recently been focused on in many projects, change the way of thinking in the development and management of urban fringes and does this transpire in the field ? Although the idea of creating these fringe areas is becoming increasingly widespread in urban planning documents, namely at the local level, in operational terms this is far from being the case and this shows the gap that exists between the discourse and reality.